A randomized, double-blind, placebo-controlled trial to assess prevention of mood episodes with risperidone long-acting injectable in patients with bipolar I disorder - Vieta, E.; Montgomery, S.; Sulaiman, A.H.; Cordoba, R.; Huberlant, B.; Martinez, L.; Schreiner, A. (Elsevier, 2012)
The efficacy and safety of risperidone long acting injectable (LAI) for preventing recurrence of mood episodes in patient with bipolar| disorder was evaluated in a randomized, placebocontrolled study. After a 12 week pen label period with risperidone LAI (n=560), patient who did not experience a recurrence entered an 18 month randomized, double-blind period with risperidone LAI(n=132)orplacebo(n=135) a third treatment arm (n=131) was randomized to oral olanzapine (10mg/day) for reference and exploratory comparisons. The primary efficacy endpoint was time to recurrence of any mood episode for risperidone LAI versus placebo in the double-blind period(Kaplan Meieranalysis).Additional efficacy endpoints included Young Mania Rating Scale,Montgomery–Asberg Depression Rating Scale and Clinical Global Impression. During the double-blind period,dosing was fixed at patients’ final open-label dose(25mg,66%ofpatients; 37.5mg,31%;50mg,4%). The primary outcome demonstrated a median time to mood episode recurrence of 198day in the place boarm, where as the median was not reached in the risperidone LAI arm (p=0.057). Time to recurrence of any mood episode was significantly longer with risperidone LAI versus placebo(log-rank test stratified by regiononly, p=0.031);the difference was significant for time to recurrence of elevated mood episodes (p=0.005)but not depressive episodes (p=0.655). Significant improvement of manic symptoms and global.